Impact factors and novel strategies for improving biohydrogen production in microbial electrolysis cells. (February 2022) - Cheng, Dongle; Ngo, Huu Hao; Guo, Wenshan; Chang, Soon Woong; Nguyen, Dinh Duc; Zhang, Shicheng; Deng, Shihai; An, Ding; Hoang, Ngoc Bich
Graphical abstract: Highlights: Novel strategies for inhibiting methanogens in MECs are reviewed. Biocathodes are promising alternatives to noble metal catalytic cathodes. Advanced MEC systems can enhance low-cost biohydrogen production. Challenges and perspectives concerning biohydrogen production were clearly stated. Abstract: Microbial electrolysis cell (MEC) system is an environmentally friendly method for clean biohydrogen production from a wide range of biowastes owing to low greenhouse gas emissions. This approach has relatively higher yields and lower energy costs for biohydrogen production compared to conventional biological technologies and direct water electrolysis, respectively. However, biohydrogen production efficiency and operating costs of MEC still need further optimization to realize its large-scale application. This paper provides a unique review of impact factors influencing biohydrogen production in MECs, such as microorganisms and electrodes. Novel strategies, including inhibition of methanogens, development of novel cathode catalyst, advanced reactor design and integrated systems, to enhance low-cost biohydrogen production, are discussed based on recent publications in terms of their opportunities, bottlenecks and future directions. In addition, the current challenges, and effective future perspectives towards the practical application of MECs are described in this review.